(untitled) (Research, Society and Development, 2022)
Precariousness of health care, difficulties in emergency care affect society and prevent the immediate resolution of their health problems. Thus, when disease is present, the community resorts to different means to solve it, such as self-medication practice. The present study aimed to discuss quantitative and qualitative data resulting from a community intervention project involving Healthcare Units users and to promote pedagogical reflections in medical students professional training. This is a quantitative-qualitative cross-sectional study idealized from an intervention project focused in the conversation wheels. Absolute and relative frequency analyses were performed by Jamovi® program. The data obtained as a result of experiences from the project and information collected in all conversation rounds. It was recorded that 73% of Healthcare Units users knowing the self-medication risks, but even so, this practice is reported by 89% of them. The main reasons for self-medications: convenience in acquisition (72.3%), delay in outpatient care (33.2%) and difficult access to health professionals (27.7%). It was also observed that strategies used in the project made possible to promote social reflections through interactive dialogues focused on the causes and consequences of self-medication linking the community problems to the teaching-learning process of the students, resulting in a closer relationship between the students and community.